2010
DOI: 10.2166/wst.2010.823
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of first flush to improve the water quality in rainwater tanks

Abstract: Although most Australians receive their domestic supply from reticulated mains or town water, there are vast areas with very low population densities and few reticulated supplies. In many of these areas rainwater collected in tanks is the primary source of drinking water. Heavy metals have recently become a concern as their concentration in rain water tanks was found to exceed recommended levels suitable for human consumption. Rainwater storage tanks also accumulate contaminants and sediments that settle to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…Martinson and Thomas (2005) recommend values varying from 1.0 to 8.5 mm according to the mean runoff turbidity on wet days following at least 3 dry days, and the intended turbidity level for the rainwater in the tank. Kus et al (2010) obtained that bypassing the first 2 mm of rainfall gives a rainwater quality compliant with most of the parameters of the Australian Drinking Water Guidelines (ADWG) standards, with the exception of lead and turbidity, which required 5 mm of first-flush to meet these standards. In summary, by using a well-regulated fistflush deviation device, the quality of the harvested rainwater can be improved dramatically.…”
Section: First Flush Deviation and Rainwater Contamination During Stomentioning
confidence: 99%
“…Martinson and Thomas (2005) recommend values varying from 1.0 to 8.5 mm according to the mean runoff turbidity on wet days following at least 3 dry days, and the intended turbidity level for the rainwater in the tank. Kus et al (2010) obtained that bypassing the first 2 mm of rainfall gives a rainwater quality compliant with most of the parameters of the Australian Drinking Water Guidelines (ADWG) standards, with the exception of lead and turbidity, which required 5 mm of first-flush to meet these standards. In summary, by using a well-regulated fistflush deviation device, the quality of the harvested rainwater can be improved dramatically.…”
Section: First Flush Deviation and Rainwater Contamination During Stomentioning
confidence: 99%
“…Comparing with the results of Mendez et al (2011), it is clear that the rainwater quality depends on the location. Kus et al (2010a) found that diverting the first 2 mm of rainfall assures compliance with the Australian Drinking Water Guidelines (ADWG) standards except for lead and turbidity, which required bypassing approximately the first 5 mm of rainfall. A first flush system improves the physicochemical quality of collected rainwater but it cannot avoid microbial contamination of stored rainwater (Gikas and Tsihrintzis, 2012).…”
Section: Previous Studiesmentioning
confidence: 99%
“…For frequency analysis of dry duration, rainfall events below 2 mm were set as dry days. Previous studies conducted by (Guo and Baetz, 2007) and (Kus et al, 2010) have shown that 2 mm of first flush can significantly improve quality of rainwater collected. (Martinson and Thomas, 2005) showed that each 1 mm of rainfall diverted in first flush can roughly reduce 50% of remaining turbidity load from collected rainwater.…”
Section: Frequency Analysismentioning
confidence: 97%